Compact Nanofilters Based on Plasmonics Waveguide With Archimedes’ Spiral Nanostructure - Yuncai Feng (IEEE Photonics Journal, 2016)
A compact plasmonic nanofilter based on the metal-insulator-metal (MIM) waveguide with an Archimedes' spiral structure is proposed and demonstrated by the finite-difference time-domain (FDTD) method. The simulation results indicate that the transmission valley and peak can be tuned by the rotation angle θ of the right-handed Archimedes spiral structure and the number of channels can be adjusted by number of right-handed Archimedes spiral rings. The characteristics of the transmission spectra could be explained by the resonant condition, which is in good agreement with the FDTD numerical simulation. The unique feature may have many potential applications in filter, sensor, and photonic integrated circuits.